2011
DOI: 10.1007/s11274-011-0852-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of formulated root endophytic fungus Piriformospora indica and plant growth promoting rhizobacteria fluorescent pseudomonads R62 and R81 on Vigna mungo

Abstract: In the present investigation, the effect of three beneficial organisms (root endophytic fungus Piriformospora indica (Pi) and pseudomonads strains R62 and R81) and their four different consortia (Pi+R62, Pi+R81, R62+R81, Pi+R62+R81) was investigated on the plant Vigna mungo through their inorganic carrier-based (talcum powder and vermiculite) formulations. All the treatments resulted in significant increase in growth parameters under glasshouse as well as field conditions and showed a consistency in their perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
28
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 30 publications
(39 reference statements)
5
28
0
Order By: Relevance
“…Results of the current investigation suggest that mixed inoculation and inoculation with the co-culture of P. indica and B. pumilus are more efficient than single inoculation of the biological agents for improving seedling growth in tomato. Previous reports involving other crops also supported the idea of co-inoculation of P. indica with beneficial bacteria to achieve greater plant growth (Meena et al 2010;Sarma et al 2011;Kumar et al 2012). …”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Results of the current investigation suggest that mixed inoculation and inoculation with the co-culture of P. indica and B. pumilus are more efficient than single inoculation of the biological agents for improving seedling growth in tomato. Previous reports involving other crops also supported the idea of co-inoculation of P. indica with beneficial bacteria to achieve greater plant growth (Meena et al 2010;Sarma et al 2011;Kumar et al 2012). …”
Section: Discussionmentioning
confidence: 70%
“…P. indica has been applied with beneficial bacterial strains such as PGPR as a mixed inoculum for mung bean and tomato. This resulted in improved growth response and disease suppression ability (Sarma et al 2011;Kumar et al 2012). Improved plant growth in chick pea has also been reported for the combined inoculation involving P. indica and the phosphate solubilizing bacterium Pseudomonas striata (Meena et al 2010).…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…The number of studies investigating the efficacy of such combined inoculations is growing, with variations in the number of microorganisms and the nature of the combinations (PGPR strains only, PGPR and fungi, etc. ; Cassán et al, 2009; Couillerot et al, 2012; Kumar et al, 2012; Walker et al, 2012). Field inoculation of sorghum with fluorescent Pseudomonas strains alone or in combination with arbuscular mycorrhizal fungi showed a better effect when in presence of the latter (Kumar et al, 2012).…”
Section: Expression Of Plant-beneficial Functions Of Pgpr In the Rhizmentioning
confidence: 99%
“…Despite this strong indication of a direct contribution of P. indica to plant P nutrition, experimental results on agricultural crops have been inconsistent. While in tobacco, barley and green gram, colonization by P. indica did not increase P content of plants despite plant growth promotion (Barazani et al 2007;Achatz et al 2010;Ray and Valsalakumar 2010), chickpea and black lentil plants showed higher P content (Nautiyal et al 2010;Kumar et al 2012). This inconsistency may be partly explained by differences in experimental conditions (Fakhro et al 2010) and highlights the need for further research.…”
Section: Introductionmentioning
confidence: 99%